The PROMISES study: a mixed methods approach to explore the acceptability of salivary progesterone testing for preterm birth risk among pregnant women and trained frontline healthcare workers in rural India. Issue 1 (8th January 2021) - Ashworth, Danielle; Sharma, Pankhuri; Silverio, Sergio A; Khan, Simi; Kathuria, Nishtha; Garg, Priyanka; Ghule, Mohan; Shivkumar, V B; Tayade, Atul; Mehra, Sunil; Shivkumar, Poonam V; Tribe, Rachel M
Abstract : Introduction: India has an overall neonatal mortality rate of 28/1000 live births, with higher rates in rural India. Approximately 3.5 million pregnancies in India are affected by preterm birth (PTB) annually and contribute to approximately a quarter of PTBs globally. Embedded within the PROMISES study (which aims to validate a low-cost salivary progesterone test for early detection of PTB risk), we present a mixed methods explanatory sequential feasibility substudy of the salivary progesterone test. Methods: A pretraining and post-training questionnaire to assess Accredited Social Health Activists (ASHAs) (n=201) knowledge and experience of PTB and salivary progesterone sampling was analysed using the McNemar test. Descriptive statistics for a cross-sectional survey of pregnant women (n=400) are presented in which the acceptability of this test for pregnant women is assessed. Structured interviews were undertaken with ASHAs (n=10) and pregnant women (n=9), and were analysed using thematic framework analysis to explore the barriers and facilitators influencing the use of this test in rural India. Results: Before training, ASHAs' knowledge of PTB (including risk factors, causes, postnatal support and testing) was very limited. After the training programme, there was a significant improvement in the ASHAs' knowledge of PTB. All 400 women reported the salivary test was acceptable with the majority finding it easy but not quick or better than drawing blood. For the qualitative aspects of the study, analysis of interview data with ASHAs and women, our thematic framework comprised of three main areas: implementation of intervention; networks of influence and access to healthcare. Qualitative data were stratified and presented as barriers and facilitators. Conclusion: This study suggests support for ongoing investigations validating PTB testing using salivary progesterone in rural settings.